Dreaming about the body: Daniel 2:32–35 interpreted from a psychoanalytical perspective - Zwan, Pieter van der (HTS teologiese studies, 2018)
Just as the text is layered by redactional processes and its effects by reception processes, so different meanings of the statue of a human body in Nebuchadnezzar’s dream can be psychoanalytically ‘excavated’. Following a typical psychoanalytical dream interpretation, the possibility has therefore been explored of the body referring to the king as an individual before it was reinterpreted as a societal, collective body, the latter serving as a defence against the anxiety which the former would cause. Re-experiencing these common, human, unconscious anxieties and processing them could facilitate psychological healing and health, especially in the postmodern, pluralistic and eco-threatened context, which the dream seems to adumbrate.